(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: the main purpose of this longitudinal study was to determine the impact of risky single occasion drinking (RSOD) frequency on alcohol dependence and drinking consequences reported 15 months later. METHODS: As a baseline sample, 5,990 young men were assessed on their drinking habits including the frequency of RSOD. Of them, 5,196 were reassessed at follow-up 15 months later on RSOD frequency, alcohol dependence and alcohol related consequences in thze interceding year. Drop out biases were investigated. RESULTS: Around 45% of the baseline participants reported regular RSOD (every month or more frequently). Despite the fact that RSOD distribution was generally stable during the initial sample, 47.4% reported a variation of their RSOD frequency 15 months later. Around 25% of the sample reported reduced RSOD frequency. Nonetheless, occasional RS drinkers were more likely to become regular (monthly) RSO drinkers at follow up. Daily and weekly RSOD were associated with high proportions of alcohol dependence and detrimental consequences of drinking. Surprisingly, abstainers at baseline were more likely to be at risk of alcohol dependence and consequences at follow up than non-RSO drinkers. CONCLUSIONS: Despite the fact that alcohol abstinence is logically the best way to avoid the detrimental consequences of alcohol drinking, abstainers at baseline reported as many problems due to alcohol use at follow up as occasional or monthly RSO drinkers. The few participants who had become RSO drinkers during the follow up period were indeed likely to engage in detrimental behaviour. Non-RSO drinkers had the fewest problems due to alcohol use. This substantiates the early occurrence of drinking consequences among inexperienced RSO drinkers.